PENGARUH KUALITAS AUDIT DAN KOMITE AUDIT TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR YANG TERCATAT DI BURSA EFEK INDONESIA - Ryu Ulina; Roza Mulyadi; Mazda Eko Sri Tjahjono (Tirtayasa Ekonomika, 2018)
This study aims to analyze the effect of the Audit Quality and Audit Commite Characteristics on Earnings Management. Variables in this study consisted of an audit quality as measured by the size of public accounting firm, industry specialist auditors and audit tenure. While audit committee are measured by audit committee size, financial expertise and the number of audit commite meetings. The modified Jones Models is used to measure discrectionary accruals (the proxy for earnings management).The sample used in this study were taken by purposive sampling method. The sample used in this research was the secondary data from annual report of manufacturing company which listed on Indonesia Stock Exchange in 2013-2016. After reduction with criteria set at 39 companies in the sample. Techniques of analysis in this study using linear regression analysis with SPSS version 20. The result of this research showed that the variable Public Accounting Firm had positive and significant influence on earnings management. Meanwhile, the variable industry specialist auditors, audit tenure, size of audit committee,  financial expertise and the number of audit commite meetings had not significant influence to the earnings management.